Primo Levi’s dystopian science fiction and the new coronavirua: the formal defect of technology - Maciera, Aislan Camargo; Massi, Luciana [UNESP]; Leonardo Junior, Carlos Sergio [UNESP] (Univ Federal Santa Maria, 2022)
The new coronavirus pandemic has made the idea that we are living in the eminences of a dystopia. Instigated by this idea, we explore in this essay the potential of dystopian science fiction texts to tension the notion of scientific truth by omitting information and generating uncertainties about the reality, involving technological artifacts that condition the possibilities of life and sociability, as in the novel The machine stops by E. M. Forster. Based on the short story Protection from the book Formal defect by Primo Levi - Jew, chemist and survivor of Shoa -, we discuss his perception of science and we establish a parallel with our context approaching technology as a restriction on freedom and truth and as an extension that limits human life. We hope this essay may help this literary subgenre to continue fulfilling their alert role for the imminent dangers of our society.
Keywords: Science fiction; Dystopia; Primo Levi; Coronavirus; Technology